SOFT SYSTEM METHODOLOGY AND HUMAN RESOURCE MANAGEMENT IN DESIGNING PUBLIC PARK - Silia silia Yuslim; Hendrik Sulistio (International Journal on Livable Space, 2019)
ABSTRACT In DKI Jakarta, the quantity and quality of public parks need to be increased since they are not well cared of as most public spaces which resulted in the absence of visitors. Hypotheses arise that this condition may be related to inaccurate public park management. This paper is an attempt to acquire a conceptual framework related to competency requirements needed in designing public parks that focus on Soft System Methodology and Resource Management. This is a literature study coupled with interviews with those who are involved in the provision and use of public parks. Through Delphi's analysis, it reveales that a successful design of public park entails non-technical competency requirements related to "building relationships" involved with all parties integrated. Keyword: Project Human Resource Management, Public Park Design, Soft System Methodology